Avaliação da circularidade de fabricantes de celulose e papel que adotaram tecnologias da indústria 4.0: estudo de casos múltiplos - Souza, Gabriel Luis Victorino (2023)
The industries in the pulp and paper sector are under pressure to reduce emissions, as they are among the most energy intensive in the world. As pulp and paper manufacturing technology has evolved over time to meet demands, the use of inputs has intensified, resulting in increased environmental impacts. Despite this, the sector stands out in global industrial and economic development, and has adopted strategies to alleviate concerns about its impacts as responses to the problems faced. Thus, circular economy practices have been adopted to reduce the use of inputs, recycling and reusing discarded materials. Regarding industry 4.0 technologies, the sector has started the process of digital transformation, where proposals for the application of predictive controls of failures and product quality, among others, have been tested. So, as both themes are seen as industrial paradigms, the investigation of the relationship between circular economy practices and industry 4.0 technologies generates relevant discoveries for knowledge. Therefore, the study aimed to evaluate the circularity of pulp and paper manufacturers that adopted industry 4.0 technologies. For that, the adopted research method was a study of multiple cases in three large world leading companies in paper manufacturing. This way, in order to evaluate the circularity index, it was necessary to compare the results of the evaluations of the environmental impacts of the mass intensity factors before and after the adoption of industry 4.0 technologies. Then, based on input reductions, an economic assessment with return on investment was made, indicating that this research offers applicability, as it presents economic opportunities and investment feasibility in industry 4.0 technologies. Regarding the environment, this research reports a reduction in the use of primary raw materials (virgin fibers) and increased use of secondary raw materials (recycled fibers), in addition to reductions in starch, steam and electricity. As a theoretical contribution, this study presents opportunities that cover the identified gaps, showing how the adoption of industry 4.0 technologies stimulates the circularity of resources used in pulp and paper production. Therefore, the application of industry 4.0 technologies for predictive control of paper quality contributes to a green future, positively affecting the sector, since opportunities for the environment directly benefit society.